Students' experiences of anxiety in an assessed, online, collaborative project. (January 2020) - Hilliard, Jake; Kear, Karen; Donelan, Helen; Heaney, Caroline
Abstract: Collaborative learning activities have become a popular method in online education to encourage active learning and equip students with team working skills that are highly valued by employers. However, past research has identified that working with other students online has the potential to cause anxiety for learners, particularly when work is being assessed. There is concern that, as well as the emotional distress this may cause, anxiety may affect students' participation and performance in these activities. This paper investigates these issues by exploring part-time distance learners' experiences of a group project where they were required to collaborate online to create a wiki resource and a website. An online survey and interviews were conducted with students who had recently completed the project. Results revealed that anxiety was commonly experienced, and causes of anxiety included relying on 'unknown others', fear of negative evaluation, and worries about non-active group members. It was found that anxiety reduced over the course of the project, as feelings of uncertainty were resolved. Findings also revealed that, although anxiety is often viewed to have detrimental consequences, more learners perceived anxiety to have had a facilitative effect on participation and performance than a debilitative one. Students who employed problem-focused coping strategies, rather than avoidance coping ones, were more likely to experience facilitative effects. These findings will be of value to educators who are designing and running online collaborative activities, and students who are participating in them. Highlights: Investigates effects of anxiety on participation in an online collaborative project. Feelings of uncertainty were a major cause of anxiety for learners. Anxiety reduced over the course of the collaborative project. Facilitative effects of anxiety were more common than debilitative effects. Facilitative effects were associated with problem-focussed coping strategies.